Biotransformation of Dehydroepiandrosterone by Penicillium olsonii MRC500780 - Mena Albayaty; Ali Kuru (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This work reported the biotransformation of dehydroepiandrosterone 1 with Penicillium olsonii MRC500780. Structure determinations revealed that biotransformation of 1 by Penicillium olsonii MRC500780 afforded androst-4-ene-3,17-dione 2, 15α-hydroxyandrost-4-ene-3,17-dione 3, 3β,7β-dihydroxyandrost-5-ene-17-one 4, 3β,7α-dihydroxyandrost-5-ene-17-one 5, and 15α,17β-dihydroxyandrost-4-ene-3-one 6. This fungus primarily isomerized the starting material in terms of the double bond and the hydroxyl group at 3β oxidised, then hydroxylated it at the C-15α position and reduced it at the C-17 position; also, hydroxylations at the C-7α position and C-7β position were observed.